The impact of working from home on the German office real estate market - Simon Krause; Andreas Trumpp; Tobias Dichtl; Susanne Kiese; Alexander Rutsch (EconPol Forum, 2024)
A quarter of the workforce regularly works from home, oftentimes blending office and remote work. The office market is undergoing a stress test, with challenging conditions expected to persist. The permanent shift toward working from home (WFH) is expected to decrease long-term office space demand by around 12 percent. In industries with high WFH rates, new office leases show a flight to quality with higher rents. An office building's ability to meet the growing "new work" demands is now a key leasing factor.
Keywords: 330